HUBUNGAN POLA USAHA KELAPA DALAM DALAM DAN HUBUNGANNYA DENGAN PENDAPATAN USAHATANI DI KECAMATAN MENDAHARA KEBUPATEN TANJUNG JABUNG TIMUR - Nurchaeni, Dewi Sri; Wahyuni, Ira (JALOW | Journal of Agribusiness and Local Wisdom, 2019)
This study aims: 1) to find out the pattern of the coconut business in which farmers work, 2) to analyze the amount of income from the coconut farming in each business pattern, 3) to analyze the relationship between the pattern of coconut business in the farmer and the income of coconut farming in the Mendahara District, East Tanjung Jabung Regency. The number of respondents was 60 coconut farmers. Sampling is done by simple random sampling method.. The analysis technique used is descriptive and quantitative analysis. From the results of the study, it was found that there were 5 (five) patterns of coconut business in which farmers carried out and the most cultivated by farmers were coconut business patterns in areca nut and coconut business patterns in monoculture. There is no relationship between the income of coconut farming in received by farmers between monoculture and polyculture business patterns. The frequency with which farmers get high or low income from coconut farming in monoculture is the same as in polyculture. Keywords: Coconut Farmers, Business Patterns, Farm Income